Neural fate commitment of rat full-term amniotic fluid stem cells via three-dimensional embryoid bodies and neurospheres formation - Azmi, Nuratiqah; Mustaffa Al Bakri, Siti Sarah; Khor, Winnie; Hamzah, Siti Nurusaadah; Ferdaos, Nurfarhana; Ling, King-Hwa; Nordin, Norshariza (Elsevier, 2023)
Full-term amniotic fluid stem cell (AFSC) is an underexplored reserve of broadly multipotent stem cells with potential applications in cell replacement therapy. One aspect worth exploring is the potential of AFSCs to differentiate into neural lineages. Previously, we have shown that full-term AFSC lines established from term gestation amniotic fluid, known as R3 and R2, differentiated into neural lineage through the monolayer adherent method suggesting their neurogenic potential. The neural commitment of the cells through the formation of multicellular aggregates has never been shown before. Here, we explored the ability of R3 to commit to neural fate via the formation of three-dimensional multicellular aggregates, namely embryoid bodies (EBs) and neurospheres, exhibiting distinct characteristics resembling EBs and neurospheres as obtained from other published pluripotent and neural stem cells (NSCs), respectively. Different cell seeding densities of the cells cultured in their respective induction medium generated two distinct types of aggregates with the appropriate sizes for EBs (300–350 µm) and neurospheres (50–100 µm). The neurospheres expressed a significantly high level of Nestin than EBs. However, EBs stained positive for TUJ1, suggesting the presence of early post-mitotic neurons representing the ectodermal lineage. In contrast, the presence of the NSC population in neurosphere culture was validated with positive expression of Sox1. Notably, dissociated cells from both aggregates differentiated into MAP2-positive neural cells, highlighting the ability of both types of multicellular aggregates to commit to the neural fate. In conclusion, this study highlights the first evidence of neurosphere formation from full-term AFSCs in addition to neural fate commitment via EBs formation. Findings from this study allow researchers to select the suitable approach for neural cell generation and expansion according to research needs.